DIFFERENTIAL EFFECT OF EDUCATION LEVELS AND BUSINESS EXPERIENCE ON INNOVATIVE CULTURE OF MICRO, SMALL, AND MEDIUM ENTERPRISES’ OWNERS - Abolaji Olubenga, Bukki; Adeolu Oludare, Olatoye; Fehintola Romi, Lemo; Ganiyu Akanbi, Bello (INTI International University, 2023)
This study examined the differential effect of education level and business experience on the innovative culture of micro, small and medium-scale enterprises (MSMEs) owners in South-West Nigeria. Two hypotheses were formulated and knowledge-based view theory was used. The study adopted the descriptive survey research design. The sample comprised one thousand, three hundred and eighty-two (1382). Data were collected using instruments titled “Education, Experience level and innovative Culture Questionnaire (r = 0.68). Data were analysed using descriptive statistics and analysis of variance (ANOVA). The results showed a significant difference in the innovative culture of MSME Owners’ based on level of education, and no significant difference existed in the innovative culture of MSME Owners based on level of experience. Based on the findings, it was recommended, among others, that government should ensure that the policy to build an entrepreneurial spirit of all students, irrespective of their level, should be well supervised. The policy will give the economy a vibrant youth equipped with innovative practices to boost the economy. The government can help enforce training, seminars, and refreshers courses for MSMEs Owners; this will go a long way in motivating the innovators to keep injecting new ideas into their respective organizations.